Efeito do estresse do viajante habitual urbano na produtividade de executivos das empresas em uma metrópole - Kobayashi, Andréa Regina Kaneko (2019)
Accelerated urbanization, disorderly growth of cities, and encouraging of the use of cars lead to several problems: traffic congestion, social inequalities, air pollution and noise, inequality in access to urban infrastructure, among others. In the megacity of São Paulo, we identified the crisis of urban mobility or urban immobility, which can bring physical and mental health problems, such as the commuter stress. This stress can be caused by frequent exposure to hours of congestion at home-work-home commuting. In the theoretical review, some studies on loss of macroeconomic productivity or loss of productivity of manual workers were found. Only evidence was found that the effects of traffic can affect the workplace of knowledge workers such as executives. The general objective of this thesis is to identify the effects of commuter stress on the executive productivity of a Brazilian megacity. The theoretical framework presents studies on the debilitating effects of stress, urban mobility problems in a Brazilian megacity, executive productivity and stress coping strategies. For this reason, we develope two articles for this present thesis: Article 1 - Validation of the commuter stress scale, and Article 2 - Model. In Article 1 we describe the results of a study that aimed to validate the commuter stress scale (proposed by Evans, Wener & Phillips, 2002), translated from English into Portuguese with semantical validation for the Brazilian context. According to Exploratory Factor Analysis, the scale studied was validated in Portuguese language. In Article 2 we describe the results of a study that aimed to: relate the effects of commuter stress to the performance of executives of a Brazilian megacity. In order to reach this goal, we used four scales in a quantitative research: Commuter stress (Evans et al, 2002), Fadigue (Chalder et al, 1993), Burnout (Maslach, 1996) and Stanford Presenteeim Scale SP-6 Koopman et al, 2002). The questionnaires were answered by executives who do daily home-work-home transportation with automobiles in São Paulo/SP. The results point to the commuter increases fatigue and burnout of the executives, which in turn diminishes their productivity.